(untitled) (France, 2018)
Education for Sustainable Development (ESD) is globally acknowledged as a powerful driver of change, empowering learners to make decisions and take actions needed to build a just and economically viable society respect ful of both the environment and cultural diversity.
Keywords: Giáo dục,Education